STUDENTS HAVE DIFFICULTY SOLVING PROBLEMS DUE TO COGNITIVE DISSONANCE - Umarov N. N. (Modern American Journals, 2025)
This article provides information on cognitive dissonance in students and the difficulties in solving problems caused by it, as well as pedagogical technologies used to overcome them.
Keywords: Cognitive dissonance, self-concept, critical thinking technology, constructive dialogue technology, cognitive modeling technology, reflexive learning technology.